Bimbingan Konseling Keluarga Berdasarkan Al Quran; Solusi Mewujudkan Keharmonisan Keluarga: Family Counseling guidance Based on The Quran; Solutions to Achieve Harmony in The Family - Zamroni Wafa; Asep Maskur (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2021)
This article explores family counseling using a Qur'anic approach as an effort to promote harmony within the family. The increasing complexity of modern family issues requires a comprehensive and multidimensional approach. Rooted in divine revelation, the Qur'anic approach offers a unique perspective in understanding and addressing various family dynamics. Family counseling based on the Qur'an not only focuses on problem-solving but also emphasizes the holistic development of both individuals and the family, grounded in the principles of divinity, humanity, and justice. The purpose of this study is to examine the relevance of Qur'anic values to the practice of family counseling. This research employs a qualitative descriptive-analytical method. Data were collected through library research, using documentation techniques involving the review of books, journals, and online media related to the study's focus. The findings indicate that integrating Qur'anic values into the counseling process can strengthen the spiritual, moral, and ethical foundations within the family. As a result, it fosters effective communication, empathy, and mutual understanding among family members.